Using environmental DNA metabarcoding to map invasive and native invertebrates in two Great Lakes tributaries. Issue 3 (16th November 2019) - Mychek‐Londer, Justin G.; Balasingham, Katherine D.; Heath, Daniel D.
Abstract: Background: Aquatic invasive species (AIS) threaten ecosystems and native species. Methods: To determine spatial distributions of at‐risk native taxa and AIS in two biologically diverse Laurentian Great Lakes tributaries, we extracted environmental DNA (eDNA) from water samples and used a universal PCR primer set targeting the CO1 gene for metabarcoding of selected taxa. We sampled 43 sites for eDNA in each of the Grand and Sydenham rivers in southwestern Ontario. Results: We assigned sequences to 49 taxa at the species level and four mollusks to genus level. Detected AIS included two oligochaete worms ( Branchiura sowerbyi, Potamothrix moldaviensis ), a freshwater jellyfish ( Craspedacusta sowerbyi ), a calanoid copepod ( Skistodiaptomus pallidus ), and a bivalve dreissenid mussel ( Dreissena rostriformis bugensis ). All but D. r. bugensis were previously unreported in these tributaries. Detected native mollusks included one globally endangered species the rayed bean ( Villosa fabalis ), one provincially listed threatened species the maple leaf mussel ( Quadrula quadrula ), and several other at‐risk and unique mollusk species of special interest in Ontario, Canada, and the United States (e.g., Sphaerium fabale, Pyganodon grandis ). At several sampling sites in each river, AIS eDNA overlapped with or was near to sites with detections of at‐risk native mollusks. Most AIS and some native taxa demonstrated clustered detection patterns within each river. However, in some cases, independent detections of individual species occurred at individual sites within each river that were relatively far apart. Our findings should be interpreted with some caution due to the limitations of the aquatic "universal" primer set and the availability of comprehensive reference sequence databases. Conclusion: Results from eDNA metabarcoding in our study helped reveal invertebrate AIS and at‐risk species distributions and will help direct approaches for conserving biodiversity in each of these Great Lakes tributaries. Abstract : We used metabarcoding of environmental DNA (eDNA) sampled from two major Great Lakes tributaries to map invasive and native invertebrate species. eDNA signatures for newly documented invasive species and threatened and endangered native taxa eDNA were documented. Species showed clumped and independent distributions, and results will help to better understand potential AIS impacts at areas where they overlapped with at‐risk native species.